Expression of Cathepsins B, D, and G in WHO Grade I Meningioma - Rahman, Rosanna M. A.; van Schaijik, Bede; Brasch, Helen D.; Marsh, Reginald W.; Wickremesekera, Agadha C.; Johnson, Reuben; Woon, Kelvin; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2019)
Aim: We have recently demonstrated the presence of tumor stem cells (TSCs) in World Health Organization (WHO) grade I meningioma (MG) localized to the microvessels, which expresses components of the renin-angiotensin system (RAS). The RAS is known to be dysregulated and promotes tumorigenesis in many cancer types, including glioblastoma. Cathepsins B, D and G are isoenzymes that catalyze the production of angiotensin peptides, hence providing bypass loops for the RAS. This study investigated the expression of cathepsins B, D and G in WHO grade I MG in relation to the putative TSC population we have previously demonstrated. Methods: 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining with antibodies for cathepsins B, D and G was performed on WHO grade I MG tissue samples from ten patients. Three of the MG samples subjected to DAB IHC staining underwent immunofluorescence (IF) IHC staining to investigate co-expression of each of these cathepsins using combinations of smooth muscle actin (SMA) and embryonic stem cell marker OCT4. NanoString mRNA expression analysis (n=6), Western blotting (WB; n=5) and enzyme activity assays (EAAs; n=3), were performed on snap-frozen WHO grade I MG tissue samples to confirm transcriptional activation, protein expression and functional activity of these proteins, respectively. Results: DAB IHC staining demonstrated expression of cathepsins B, D and G in all ten MG samples. NanoString mRNA and WB analyses showed transcriptional activation and protein expression of all three cathepsins, although cathepsin G was expressed at low levels. EAAs demonstrated that cathepsin B and cathepsin D were functionally active. IF IHC staining illustrated localization of cathepsin B and cathepsin D to the endothelium and SMA+ pericyte layer of the microvessels, while cathepsin G was localized to cells scattered within the interstitium, away from the microvessels. Conclusion: Cathepsin B and cathepsin D, and to a lesser extent cathepsin G, are expressed in WHO grade I MG. Cathepsin B and cathepsin D are enzymatically active and are localized to the putative TSC population on the microvessels, whereas cathepsin G was localized to cells scattered within the interstitium, These results suggest the presence of bypass loops for the RAS, within WHO grade I MG.